2009
DOI: 10.1039/b909091f
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-based development of triazole-substituted O-galactosyl aldoximes with fragment-induced affinity and selectivity for galectin-3

Abstract: A fragment-based development of 3C-triazol-1-yl-O-galactopyranosyl aldoximes led to the discovery of highly selective and high affinity (K(d) down to 11 microm) small monosaccharide based inhibitors of galectin-3. Galectin-7, 8 N-terminal CRD, and 9 N-terminal CRD bound the inhibitors only weakly. The galectin-3 selectivity was hypothesized to stem from interaction of the aldoxime moiety with a site not present in the other galectins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…2a) to further improve affinity and thus providing promise for drug development. [83] Collections of O-and C-β-d-galactosides with aglycons incorporating isoxazole-or triazole moieties that would interact with subsite D were found by Roy et al to inhibit galectin-1 with promising mM affinities and with significant selectivity over galectin-3 [68] (Fig. 6).…”
Section: Inhibitors Mimicking Glc or Glcnac Of Natural Ligands -Targementioning
confidence: 95%
“…2a) to further improve affinity and thus providing promise for drug development. [83] Collections of O-and C-β-d-galactosides with aglycons incorporating isoxazole-or triazole moieties that would interact with subsite D were found by Roy et al to inhibit galectin-1 with promising mM affinities and with significant selectivity over galectin-3 [68] (Fig. 6).…”
Section: Inhibitors Mimicking Glc or Glcnac Of Natural Ligands -Targementioning
confidence: 95%
“…Further evidence has been gathered to support the proposal that it is the quinone methide, formed by two electron reduction of prekinamycin, that is responsible for its cytostatic activity (Khdour & Skibo, 2009). A series of substituted thienopyrimidines have been synthesised and shown to be cytotoxic to a number of cancer cell lines (Snegaroff et al, 2009) and substituted O-galactosyl aldoximes were prepared as selective galectin-3 inhibitors (Tejler et al, 2009). Pyrrolidine 3,4-diols have been reported as -L-fucosidase inhibitors (MorenoClavijo et al, 2009).…”
Section: Bioactivesmentioning
confidence: 97%
“…[137] In addition, the compounds containing indole aldoximes at C1 showed high selectivity for galectin-3, where the indole group could supposedly move into a unique binding groove next to the galactosebinding site. [137] Several C3 triazole-linked [138] and C1 O-or S-linked [139] galactose modifications using aromatic moieties have been reported, but the initial molecules did not achieve the same level of haemagglutination inhibition as the lactosides. A later study found a single C1-butyl-2-enoate modification that was ,2-fold better than lactose and selective for galectin-1 over galectin-3 (Fig.…”
Section: Modified Saccharidesmentioning
confidence: 98%
“…Stemming from the work with arginine tweezers [139,142] and previous work with galactose C1 aldoximes [50,137] (described above), several modifications were made onto the C2 and C3 positions of a taloside scaffold. [51] The taloside is meant to mimic the galactose scaffold with the added benefit of an axial C2 hydroxy group, which points along the surface of galectins, increasing the effect of C2 modifications as opposed to being directed away from the protein surface in the case of galactose.…”
Section: Talose-based Inhibitorsmentioning
confidence: 99%